2006
DOI: 10.1246/cl.2006.1188
|View full text |Cite
|
Sign up to set email alerts
|

Light-induced Electron Transfer on the Single Wall Carbon Nanotube Surrounded in Anthracene Dendron in Aqueous Solution

Abstract: Light illumination of single-wall carbon nanotubes (SWCNTs) dispersed with anthracene (An) dendrons afforded the accumulation of the reduced form of methyl viologen in the presence of a hole shifter. With the helps of the fluorescence lifetime and transient absorption measurements, the charge-separation process from the excited state of the hybrides of An dendrimer to SWCNT was confirmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 7 publications
1
29
0
Order By: Relevance
“…Fluorescence quenching studies of SWNT-anthracene adducts have been reported. [9][10][11] In Table IV the binding energies of a number of pyrene derivatives are presented. As expected, due to the larger footprint of pyrene the binding energy E B is higher than for that of anthracene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence quenching studies of SWNT-anthracene adducts have been reported. [9][10][11] In Table IV the binding energies of a number of pyrene derivatives are presented. As expected, due to the larger footprint of pyrene the binding energy E B is higher than for that of anthracene.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, supramolecular (non-covalent) functionalization via π -π stacking has only a minimal effect on their electronic properties. [4][5][6][7] In this context, a range of polycyclic aromatics have been studied experimentally, including anthracene, [8][9][10][11] phenanthrene, 12, 13 pyrene, 4, 5, 14-20 tetracene, 13 pentacene, 13 and diazapentacene. 21 Recent ab initio calculations 22,23 have focussed on the adsorption of planar unsaturated aromatic molecules onto a range of small-diameter CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, aromatic molecules, such as pyrene, porphyrin, and their derivatives, can interact with the sidewalls of CNTs by means of π-π stacking interactions [139,140]. Among the main reasons to prepare dendronized CNTs, it is worth mentioning the enhancement of their dispersibility in all type of solvents, especially in water, for biological applications [92,[141][142][143][144][145][146].…”
Section: Dendronized Cntsmentioning
confidence: 99%
“…Effective anchoring groups include polycyclic aromatic species such as anthracene, 22 pyrene, 7,23 perylene, 10,21,24,25 porphyrin derivatives 26 and more complex "nanotweezer" systems. 27,28 Suitable hydrophilic moieties include carboxylate, ammonium and sulfonate salts, 9 polyethylene glycol (PEG) derivatives 23 and Newkome 7,21,24,27 and glycerol 25 dendrons.…”
Section: Introductionmentioning
confidence: 99%